Estratégias de planejamento para otimização do consumo residencial de energia elétrica: uma abordagem baseada em smart home e sistemas fuzzy - ANDRADE, Sérgio Henrique Monte Santo (Universidade Federal do Pará, 2018)
Residential energy consumption has grown steadily over the last decades, becoming a problem for companies in the electricity sector, for consumers and for the environment. The traditional measurement systems are not sufficient and have limitations in providing adequate real-time information about consumption. As also, they are not prepared to deal with variable energy costs in the context of a market with dynamic prices that depend on the energy mix. The future of electric grid, called Smart Grid, will not only be designed with measurements based on the residences, but also on the individualized equipment consumption level. From the residential side, consumers generally suffer from a lack of information on the specific equipment energy consumption impact and, consequently, on the required behavior to reduce its consumption. In this context, this work aims on a smartphone monitoring system concept, to control energy using fuzzy logic, in order to provide to the user ways to maintain his energy consumption, through consumption profiles, within the user-defined consumption patterns. The energy reduction demand through the consumption profiles working with habitant dependence degree on the electrical equipment present in the residence, promote a smaller impact on inhabitant well-being and the daily life.